Peningkatan Kreativitas Anak Kelompok B1 Melalui Kegiatan Menghias Menggunakan Teknik Kolase Payet - Anggita Yola Prastika; Usep Kustiawan; Rosyi Damayani Twinsari Maningtyas (Jurnal Pendidikan Modern, 2020)
The research objective was to find out (1) the implementation of teacher learning in the application to enhance creativity through decorating activities using sequin collage techniques, (2) increasing creativity through decorating activities using sequin collage techniques. Data is collected by observation, interview and documentation techniques. Data analysis was carried out in a qualitative descriptive manner about child and teacher activities, interviews, field notes and documents and quantitatively about improving children's creativity. Researcher's results are: (1) implementation of teacher learning in application to enhance creativity through decorating activities using sequin collage techniques, (2) decorating activities using sequin collage techniques can increase creativity